In‐vacuum long‐wavelength macromolecular crystallography. Issue 3 (1st March 2016) - Wagner, Armin; Duman, Ramona; Henderson, Keith; Mykhaylyk, Vitaliy
Abstract : The motivation for, and the first results from, the novel in‐vacuum long‐wavelength MX beamline I23 at Diamond Light Source are presented. Abstract : Structure solution based on the weak anomalous signal from native (protein and DNA) crystals is increasingly being attempted as part of synchrotron experiments. Maximizing the measurable anomalous signal by collecting diffraction data at longer wavelengths presents a series of technical challenges caused by the increased absorption of X‐rays and larger diffraction angles. A new beamline at Diamond Light Source has been built specifically for collecting data at wavelengths beyond the capability of other synchrotron macromolecular crystallography beamlines. Here, the theoretical considerations in support of the long‐wavelength beamline are outlined and the in‐vacuum design of the endstation is discussed, as well as other hardware features aimed at enhancing the accuracy of the diffraction data. The first commissioning results, representing the first in‐vacuum protein structure solution, demonstrate the promising potential of the beamline.